APPLICATION OF CASH EXPENDITURE SYSTEMS TO SUPPORT EFFICIENCY OF COSTS IN GENERAL CASHIER SECTION ON HARRIS HOTEL TUBAN - Margaretta Ayu Angria; Ni Made Ernawati; Luh Linna Sagitarini (Journal of Applied Sciences in Travel and Hospitality, 2018)
The problems that often occur in the General Section Cashier Harris Hotel Tuban is the case of cash expenditures for petty cash activities. General Cashier's section was disturbed by petty cash requests and additional expenses due to petty cash activities. The purpose of this research is to know petty cash system and procedure at General Cashier Harris Hotel Tuban and to know cost efficiency in General Cashier section related to petty cash expenditure. The method of analysis used in this research is descriptive statistical analysis method. This analysis is done by collecting and processing the data obtained thoroughly and in detail, then described so as to obtain a clear description of the facts by comparing the system and procedure cash disbursement petty cash at Harris Hotel Tuban with theory according Mulyadi (2016). The researchs’ results showed that cash disbursement system by petty cash in General Cashier at Harris Hotel Tuban was in accordance with Mulyadi theory. Petty cash system cash disbursement procedure in General Cashier's section at Harris Hotel Tuban starts from receiving reports of lack of supplies from related departments then through department supervisors, store keeper, purchasing and General Cashier for the issuance of petty cash. The level of cash dispensing system efficiency by petty cash in General Cashier Harris Hotel Tuban section in 2015 s.d in 2017 fluctuates. The inefficiencies that occur each year are due to the expenditure of petty cash beyond the budget set. While the efficiency that occurs due to petty cash spending is less than the budget set.